A multimodal clinical data resource for personalized risk assessment of sudden unexpected death in epilepsy - Li, Xiaojin; Tao, Shiqiang; Lhatoo, Samden D.; Cui, Licong; Huang, Yan; Hampson, Johnson P.; Zhang, Guo-Qiang (Frontiers in Big Data, 2022)
Epilepsy affects approximately 2-3 million individuals in the United States, a third of whom have uncontrolled seizures. Sudden unexpected death in epilepsy (SUDEP) is a catastrophic and fatal complication of poorly controlled epilepsy and is the primary cause of mortality in such patients. Despite its huge public health impact, with a 1/1000 incidence rate in persons with epilepsy, it is an uncommon enough phenomenon to require multi-center efforts for well powered studies. We developed the Multimodal SUDEP Data Resource (MSDR), a comprehensive system for sharing multimodal epilepsy data in the NIH funded Center for SUDEP Research. The MSDR aims at accelerating research to address critical questions about personalized risk assessment of SUDEP. We used a metadata-guided approach, with a set of common epilepsy-specific terms enforcing uniform semantic interpretation of data elements across three main components: 1) multi-site annotated datasets; 2) user interfaces for capturing, managing, and accessing data; and 3) computational approaches for the analysis of multimodal clinical data. We incorporated the process for managing dataset-specific data use agreements, evidence of Institutional Review Board review, and the corresponding access control in the MSDR web portal. The metadata-guided approach facilitates structural and semantic interoperability, ultimately leading to enhanced data reusability and scientific rigor. MSDR prospectively integrated and curated epilepsy patient data from 7 institutions, and it currently contains data on 2,739 subjects and 10,685 multimodal clinical data files with different data formats. In total, 55 users registered in the current MSDR data repository, and 6 projects have been funded to apply MSDR in epilepsy research, including 3 R01 projects and 3 R21 projects.